Consecutive renal biopsy in a cohort of patients with lupus nephritis of the Colombian Caribbean (2018)
Background: Renal biopsy is the gold standard for the diagnosis and classification of lupus nephritis (LN). However, a consecutive biopsy can predict the clinical course and optimize the therapeutic strategies. Objectives: To compare the histopathological findings with clinical responses. Patients and Methods: Thirty patients with active LN were included. Renal biopsies were performed at the time of diagnosis and subsequently under clinical criteria according to consensus of Spanish Society of Nephrology. The response to treatment was defined as complete response, partial responder or non-responder. The histological change in second biopsy towards LN classes I, II or III/IV-C was defined as histological response (HR). Results: In initial renal biopsy, 28 (93%) patients showed proliferative LN; III-A or A/C (n; 7), IV-A or A/C (n: 19) and mixed; III+IV/V (n; 2). LN class V was presented in two cases. The clinical response was; complete response (10%), partial response (20%), and non-response (70%). HR was manifested in 37% and non-histologic response in 63% of patients. Around 33% of patients with complete response/partial response showed active lesions in the consecutive renal biopsy. Conclusions: In Colombian Caribbean, LN is aggressive and refractory to treatment. The consecutive renal biopsy allowed to demonstrate the persistence of the activity of the lesion in almost half of the patients, which may provide additional information to create better response criteria. The consecutive renal biopsy is a tool that allows improving the evaluation of the response to treatment in the LN.